2009
DOI: 10.1111/j.1473-2165.2009.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of reported adverse events to injectable polylactic acid after recommending an increased dilution: 8‐year results from the Injectable Filler Safety study

Abstract: PLA is an injectable filler substance that may cause subcutaneous nodules in treated patients. Our data support a decreased risk of adverse reactions with an increased dilution. However, nodule formation still appears to be a characteristic feature of PLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…The safety profile of PLLA has improved dramatically over recent years with increased experience in product preparation, in selection of injection area and in injection modalities. In particular a decreased risk of adverse reactions with an increased dilution was noted in several clinical trials and in the Injectable Filler Safety Study [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of PLLA has improved dramatically over recent years with increased experience in product preparation, in selection of injection area and in injection modalities. In particular a decreased risk of adverse reactions with an increased dilution was noted in several clinical trials and in the Injectable Filler Safety Study [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of PLLA for soft-tissue augmentation are well established, with over 20 studies in more than 4000 patients [17][18][19][20]. However, several treatment sessions are required for optimal facial volume restoration, and the main concern about PLLA injection is the delayed effect of nonvisible palpable nodules and visible papules.…”
Section: Poly-l-lactic Acidmentioning
confidence: 97%
“…According to a blinded evaluator, 77 % of subjects at week 8 and 59 % of subjects at week 24 following upper and lower lip injections were considered to have a one-grade or greater change on the 5-point Medicis Lip Fullness Scale. For subjects receiving additional injections for correction of perioral rhytides, there was a statistically significant and clinically meaningful improvement in perioral rhytides as assessed by the blinded evaluator at weeks [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. No serious adverse events occurred.…”
Section: Restylane ò Silkmentioning
confidence: 99%
“…Even with increased dilution of poly-l-lactic acid, the study concluded that adverse events still occur and advised that poly-l-lactic acid continue to be monitored for safety. 44 The other study on the Berlin Injectable Filler Safety registry characterized adverse reactions to DermaLive (Dermatech, Paris, France), a fixed combination of hydroxyethylmethacrylate and ethylmethacrylate with hyaluronic acid. The study identified 30 patients who were treated with this filler.…”
Section: Adverse Event Reportingmentioning
confidence: 99%